2016
DOI: 10.1103/physreva.93.022317
|View full text |Cite
|
Sign up to set email alerts
|

Information-theoretical analysis of topological entanglement entropy and multipartite correlations

Abstract: A special feature of the ground state in a topologically ordered phase is the existence of large scale correlations depending only on the topology of the regions. These correlations can be detected by the topological entanglement entropy or by a measure called irreducible correlation. We show that these two measures coincide for states obeying an area law and having zero-correlation length. Moreover, we provide an operational meaning for these measures by proving its equivalence to the optimal rate of a partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 47 publications
4
65
0
Order By: Relevance
“…The amount of classical information that can be hidden with this scheme is then given by the JKL index. We compare this to a similar result in finite dimensions [12], where the TEE was shown to coincide with the optimal achievable rate of a (different) secret sharing scheme via the irreducible correlation. Based on this we argue that the JKL index is indeed closely related to the TEE.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…The amount of classical information that can be hidden with this scheme is then given by the JKL index. We compare this to a similar result in finite dimensions [12], where the TEE was shown to coincide with the optimal achievable rate of a (different) secret sharing scheme via the irreducible correlation. Based on this we argue that the JKL index is indeed closely related to the TEE.…”
Section: Introductionmentioning
confidence: 57%
“…Section 4 then is devoted to constructing a secret sharing scheme in the example of the toric code on the infinite plane and to explaining how it relates to the index. Furthermore we discuss how this is connected to recent work [12], where for finite two-dimensional lattice systems it was shown that there is a connection between the TEE and the irreducible correlation of certain secret sharing schemes. We also discuss the role of superselection sectors in our construction.…”
Section: Content Of This Workmentioning
confidence: 68%
See 3 more Smart Citations